2015
DOI: 10.1186/s12889-015-1564-1
|View full text |Cite
|
Sign up to set email alerts
|

Partners’ controlling behaviors and intimate partner sexual violence among married women in Uganda

Abstract: BackgroundStudies on the association between partners’ controlling behaviors and intimate partner sexual violence (IPSV) in Uganda are limited. The aim of this paper was to investigate the association between IPSV and partners’ controlling behaviors among married women in Uganda.MethodsWe used the 2011 Uganda Demographic and Health Survey (UDHS) data, and selected a weighted sample of 1,307 women who were in a union, out of those considered for the domestic violence module. We used chi-squared tests and multiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
61
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(86 citation statements)
references
References 23 publications
22
61
1
2
Order By: Relevance
“…Women in Eastern and Western Uganda were also more likely to experience sexual IPV compared to those in Central Uganda. This nding is consistent with other studies by Karamagi, Tumwine [41], Wandera, Kwagala [26] and Annan and Brier [42] where they found that structural factors, like gender inequality, devastating poverty, alcoholism and police corruption, helped sustain IPV. The social acceptance of violence as a tool to resolve con icts in relationships among some Ugandan societies alongside weak implementation of community sanctions against IPV could explain this nding.…”
Section: Discussionsupporting
confidence: 92%
“…Women in Eastern and Western Uganda were also more likely to experience sexual IPV compared to those in Central Uganda. This nding is consistent with other studies by Karamagi, Tumwine [41], Wandera, Kwagala [26] and Annan and Brier [42] where they found that structural factors, like gender inequality, devastating poverty, alcoholism and police corruption, helped sustain IPV. The social acceptance of violence as a tool to resolve con icts in relationships among some Ugandan societies alongside weak implementation of community sanctions against IPV could explain this nding.…”
Section: Discussionsupporting
confidence: 92%
“…Women in Eastern and Western Uganda were also more likely to experience sexual IPV compared to those in Central Uganda. This finding is agreeable to those in studies by Karamagi, Tumwine [40], Wandera, Kwagala [19] and Annan and Brier [41] where structural factors like gender inequality, devastating poverty, alcoholism and corruption in police were reported to sustain IPV. The social acceptance of violence as a tool to resolve conflicts in relationships for some societies in Uganda alongside weak implementation of community sanctions against IPV could explain this finding.…”
Section: Discussionsupporting
confidence: 91%
“…Women whose partners had controlling behaviors were more likely to experience all forms of IPV and similar findings have been reported in Uganda [14,15,19] and WHO multi-country study [13]. The dowry that men pay could help explain this finding since most men and the society generally view such women as a property of their husbands so long as bride price was paid.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations